VEGF polymorphisms and severity of atherosclerosis. Issue 6 (3rd June 2005) - Howell, W M; Ali, S; Rose-Zerilli, M J; Ye, S
Abstract : Introduction: Vascular endothelial growth factor (VEGF) is a potent angiogenic factor, and neovascularisation has been shown to be important in atherosclerotic plaque development. There is some disagreement as to whether VEGF acts as a pro-atherosclerotic or anti-atherosclerotic factor. In the present study we have sought to clarify this by determining genotypes and haplotypes for three reportedly functional VEGF SNPs in a large series of well documented coronary atherosclerosis patients. Methods: VEGF −2578, −1154, and −634 single nucleotide polymorphisms were genotyped in 984 subjects from the Southampton Atherosclerosis Study, using the 5′ nuclease assay for allelic discrimination ( Taq Man). Results: VEGF −2578 genotypes showed a significantly different distribution in patients without myocardial infarction when stratified according to number of diseased arteries. VEGF −2578 was also associated with mean number of stenotic segments in the same patient group. The AA genotype was a risk factor and CC was protective. These associations were significant before and after adjustment for classic risk factors, and were reflected in associations between VEGF haplotypes and the number of diseased arteries and stenotic segments. As VEGF −2578 CC has been provisionally shown to be associated with higher VEGF expression than the AA genotype, these results are consistent with a protective effect for VEGF in atherosclerosis development. Some changes in VEGF −1154 genotype frequencies were also detected, but no significant associations were detected for any one particular genotype. Conclusions: This study provides preliminary evidence that VEGF polymorphism is associated with development of atherosclerosis, possibly via regulation of VEGF expression, supporting a protective effect for VEGF in atherosclerosis. These results require replication in an independent study group, combined with study of additional candidate polymorphisms in the VEGF gene.